Whisker-reinforced high-temperature-resistant and acid-corrosion-resistant artificial stone and preparation method thereof
By combining anhydrous calcium sulfate whiskers with unsaturated resin and using a specific preparation process, the problems of reduced strength, poor acid resistance, and insufficient thermal stability of resin-based artificial stone at high temperatures have been solved, achieving high-precision heat transfer and high-strength acid-resistant artificial stone.
Patent Information
- Application Number
- CN202511251357.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-03
- Publication Date
- 2025-11-28
AI Technical Summary
Existing resin-based artificial stone suffers from decreased strength, easy deformation, weak acid corrosion resistance, and poor long-term thermal stability under high-temperature environments, making it difficult to meet the needs of high-precision decoration.
Artificial stone is prepared by combining anhydrous calcium sulfate whiskers with unsaturated resin through a specific segmented mixing and vibration degassing process, ensuring high bonding strength between the whiskers and resin, and maintaining the integrity and acid resistance of the material at high temperatures.
It maintains high strength (≥ 40 MPa) at 250 ℃, is completely resistant to 50% sulfuric acid corrosion, has a heat deformation rate ≤ 0.03 mm/m, and has extremely low internal porosity, which significantly improves the accuracy and adhesion of heat transfer printing.
Smart Images

Figure CN121021041A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of high-end decorative building material manufacturing, and particularly relates to a whisker-reinforced high-temperature-resistant and acid-erosion-resistant artificial stone and a preparation method thereof, which is particularly suitable for manufacturing precise decorative surfaces that need to withstand high-temperature transfer printing (200-230 ℃) and realizes the reproduction of patterns with micron-level precision of the transfer printing layer through whisker reinforcement. BACKGROUND
[0002] Resin-based artificial stone composites are composed of a matrix resin and a reinforcing material (i.e., a filler). In a broad sense, all organic polymer materials can be used as the matrix resin, and all fibrous and particulate substances with a strength or hardness higher than that of the matrix resin can be used as the reinforcing material. The reinforcing material requires a strength or hardness higher than that of the matrix resin and can be uniformly dispersed in the resin. Fibrous and particulate substances with high strength and high hardness can meet the requirements. With the development of science and technology, new materials are continuously developed and applied to composites. Fibrous substances such as organic natural or synthetic fibers, inorganic non-metallic fibers, and metal fibers, and particulate substances such as aluminum oxide, calcium carbonate, silicon oxide, mica flakes, and graphene, can all be used as reinforcing materials. The Mohs hardness of anhydrous calcium sulfate whiskers is 3-4, the tensile strength is 2.058 Gpa, and the elastic modulus is 176.4 Gpa. There are almost no dislocations, vacancies, and other macroscopic defects in the crystal structure that weaken the material, and the crystal integrity is close to 100%. The mechanical strength of anhydrous calcium sulfate whiskers is extremely high, and when used as a filler for artificial stone, it can greatly improve the mechanical properties of artificial stone.
[0003] Resin-based artificial stone accounts for more than 85% of the global market share, mainly using an unsaturated polyester resin and an aluminum hydroxide, quartz stone filler system (Chinese national standard GB / T 35157-2017). Although this type of material has the advantages of customizable colors and easy processing, it has the following serious defects:
[0004] (1) Insufficient temperature resistance: Aluminum hydroxide filler (ATH) decomposes at temperatures >180 ℃: 2Al(OH)3 → Al2O3 + 3H2O↑ (endothermic reaction) This process produces a large amount of water vapor, resulting in a decrease in bending strength. After 200 ℃ / 2 h treatment, the strength decreases from the initial 45-50 MPa to 28-32 MPa (decay rate > 30%), which is lower than the national standard requirement of 40 MPa (see KMG-RPT-2022-087 test report of Komei Technology Co., Ltd.); surface bubbling: water vapor pressure causes microcracks in the matrix (SEM shows pore size of 50-200 μm), and the permanent damage rate reaches 100% after hot pot placement (250 ℃) (SGS data from the sampling inspection of 12 brands). For example, patent CN107474482A;
[0005] (2) Poor acid resistance: After 24 hours of contact with 50% sulfuric acid, corrosion pits with a depth > 0.5 mm are formed on the surface, and the gloss is lost by more than 50% (ISO 4586 test), because Al(OH)3 reacts with acid to form soluble aluminum sulfate (Document DOI:10.1016 / j.ceramint.2020.08.123).
[0006] (3) Uncontrolled warping deformation: The heat deformation rate at 80 ℃ / 48 h reaches 0.1% ~ 0.15% (ASTM D696), which is far higher than the requirement of ≤ 0.05% for high-end countertops. The main reason is the mismatch between the resin curing shrinkage and the thermal expansion coefficient of the filler.
[0007] To overcome these limitations, the industry has tried various technical solutions, but all of them have bottlenecks:
[0008] (1) Wollastonite fiber reinforcement (CN107474482A): Fibers with an aspect ratio >50 cause anisotropic shrinkage, and the warpage reaches 0.25 mm / m after 10 cycles of hot and cold cycling (-20 ℃ ~ 150 ℃);
[0009] (2) Vacuum-ultrasonic combined degassing (JP2019055823): The equipment cost exceeds US$500,000 and the removal rate of microbubbles <100 μm is <50%;
[0010] (3) Nano-alumina coating (US10487231B2): After the coating peels off, the substrate corrodes rapidly, and the acid etching quality loss reaches 1.2%;
[0011] (4) Glass fiber reinforced (DE102017206): Exposed glass fiber results in a surface roughness Ra > 5 μm, which does not meet the food contact standard (FDA 21 CFR 177.2600).
[0012] Artificial stone prepared using anhydrous calcium sulfate whiskers as filler can achieve a flexural strength exceeding 40 MPa. Furthermore, the flexural strength of the artificial stone specimens continuously increases with the increase in the whisker aspect ratio. When the average aspect ratio of the whiskers is 30, the flexural strength of the prepared artificial stone reaches 47.5 MPa, exceeding the requirement of ≥ 30 MPa for quartz stone slabs in the building industry standard JC / T 908-2002. When anhydrous calcium sulfate whiskers are added to related products, their orientation is not as regular as that of long and short chopped fibers. This microscopically alters the product while making it isotropic. This has a significant impact on the quality of high-precision electronic and home appliance components. Furthermore, the application of calcium sulfate whiskers in products results in a smaller difference in longitudinal and transverse shrinkage rates, ensuring the precision of product dimensions and appearance, and preventing warping and deformation.
[0013] Calcium sulfate whiskers possess the thermal uniformity of inorganic fillers, have a melting point of 1450℃, and retain their original mechanical properties even at 900℃. Adding them to products can significantly improve their heat resistance. For example, in Chimei 757 ABS material, the matrix heat distortion temperature is 84℃, while the heat distortion temperature after calcium sulfate whisker reinforcement is 90℃. For pure PP powder to PP masterbatch, the addition of calcium sulfate whiskers can strengthen it, increasing the heat distortion temperature from 81.73℃ to 118.64℃. When anhydrous calcium sulfate whiskers are used as a filler to mix with unsaturated resin to prepare artificial stone, the heat resistance of the artificial stone slabs can be significantly improved. Artificial stone made with aluminum hydroxide or quartz as fillers loses less than 50% of its original flexural strength after heat treatment at 200℃ for 2 hours. However, artificial stone using anhydrous calcium sulfate whiskers as fillers retains more than 95% of its original flexural strength after heat treatment at 250℃ for 2 hours.
[0014] Currently, heat transfer printing on artificial stone at temperatures above 180 ℃ generally suffers from: (1) substrate thermal deformation leading to pattern misalignment (≥0.1 mm / m); and (2) surface resin softening reducing transfer resolution (<300 dpi). This invention, through anhydrous calcium sulfate whiskers and synergistic surface contour control, achieves for the first time micron-level precision maintenance (deformation <0.03 mm / m, resolution ≥400 dpi) for high-temperature transfer at 230 ℃. Major international brands such as LG HI-MACS® (aluminum hydroxide + MMA resin), DuPont™ Corian® (aluminum hydroxide + acrylic resin), and SILESTONE® (quartz stone) have heat transfer temperature limits of 195 ℃, 200 ℃, and 180 ℃, respectively, and their published resolutions are all ≤320 dpi. The Corian® 2023 processing guidelines explicitly warn that "heat transfer above 200 ℃ may cause thermal damage to the substrate." In comparison, the whisker-based artificial stone of this invention achieves a breakthrough in safe transfer at 230 ℃, with a resolution of ≥400 dpi (actually measured at 420 dpi), and its technical parameters comprehensively surpass those of existing high-end products.
[0015] Although some artificial stone patents have used calcium sulfate whiskers as fillers, the amount added is low, making it difficult to reflect the whisker characteristics. For example, patent CN103408251A provides a calcium sulfate whisker composite quartz stone slab product and its preparation method. The filler is mainly composed of granular raw materials, with an addition amount of 58% to 75%, of which whiskers account for only 5% to 10%. This low addition amount makes it difficult to reflect the performance of calcium sulfate whiskers. Furthermore, the preparation process requires mixing the filler and then grinding and dispersing it in a sand mill. Grinding significantly reduces the aspect ratio of the whiskers, diminishing their reinforcing effect.
[0016] Patent CN 105948568 B provides a method for preparing a high-strength, wear-resistant artificial quartz stone slab, which includes the addition of calcium sulfate whiskers. However, the main filler is still quartz stone, and the amount of calcium sulfate whiskers added is relatively small, with a mass fraction of only 1 to 7 parts. This also suffers from the problem that the low addition amount makes it difficult to fully utilize the performance of calcium sulfate whiskers. Patent CN107805003A provides a method for preparing a high-performance artificial quartz stone slab, in which the amount of calcium sulfate whiskers added is only 2 to 5 parts; Patent CN103204661A provides a method for preparing a high-impact artificial quartz stone slab and its production process, in which the amount of calcium sulfate whiskers added is 15 to 20 parts. Both patents suffer from the same problem.
[0017] In conclusion, current artificial stone technology faces irreconcilable contradictions in its pursuit of high performance:
[0018] (1) High temperature resistance requirement (>200 ℃) ~ Filler thermal decomposition (ATH dehydration) / whisker water content (traditional calcium sulfate whiskers) / quartz (quartz and resin have large differences in linear expansion coefficients);
[0019] (2) High filling requirements (>65%) ~ Process defects (bubble rate, warpage deformation);
[0020] (3) Precision decoration requirements (micron-level precision of heat transfer printing) ~ Insufficient thermal stability of the substrate (deformation > 0.1 mm / m, strength decrease).
[0021] In particular, there is a lack of a disruptive solution that can simultaneously meet the following requirements: (a) long-term thermal stability at 250 °C (strength retention rate > 95%); (b) zero corrosion in strong acid environments (mass loss of 50% sulfuric acid for 24 h < 0.1%); (c) near-zero defects (bubble rate < 0.1 vol%) under high-filling (> 65%) anhydrous calcium sulfate whiskers; and (d) substrate deformation rate ≤ 0.03 mm / m suitable for high-temperature heat transfer printing (200 ~ 230 °C). Summary of the Invention
[0022] This invention aims to solve key problems of existing artificial stone, such as decreased strength and easy deformation under high temperature environments (especially in heat transfer printing processes), weak resistance to acid corrosion (especially to sulfuric acid), poor long-term thermal stability, and performance degradation due to internal pore defects. To this end, a heat transfer-compatible, high-temperature resistant, acid-resistant anhydrous calcium sulfate whisker-reinforced artificial stone and its dedicated preparation method are provided.
[0023] The core characteristics of the artificial stone lie in its composition and performance: it is made of 65% to 90% anhydrous calcium sulfate whiskers and 10% to 35% unsaturated resin (preferably phthalic resin with added MMA monomer), and contains 0.2% to 2% curing agent. The anhydrous calcium sulfate whiskers need to be calcined at 620 to 650 °C, with an aspect ratio of 5 to 40, and the proportion of particles with a length of 150 to 300 μm is not less than 90%. The artificial stone must simultaneously meet the following key performance indicators: (a) after heating at 250 °C for 2 hours, the flexural strength is still ≥ 40 MPa, and the strength retention rate is ≥ 95%; (b) after contact with 50% sulfuric acid for 24 hours, there are no blemishes on the surface; (c) within a temperature range of 200 to 230 °C suitable for heat transfer printing, the substrate deformation rate is ≤ 0.03 mm / m.
[0024] Its proprietary preparation method includes the following key steps: First, segmented mixing is performed under vacuum (-0.01 ~ -0.09 MPa): the first stage is mixed at 20 ~ 30 rpm for 5 ~ 10 minutes, and the second stage is accelerated to 70 ~ 90 rpm for 15 ~ 25 minutes. Second, an innovative two-stage vacuum vibration degassing process is performed: the first stage is carried out at 25 ~ 40 ℃ with a vibration frequency of 30 ~ 50 Hz and an amplitude of 0.2 ~ 0.4 mm for 5 ~ 15 minutes; the second stage is heated to 55 ~ 65 ℃, the vibration frequency is reduced to 10 ~ 20 Hz, the amplitude is reduced to 0.05 ~ 0.1 mm, and vibration is continued for 5 ~ 10 minutes until the mirror reflection on the material surface disappears or there is no leveling in the needle scratch test, ensuring that the final closed-cell rate is ≤ 0.05 vol% and the open-cell rate is ≤ 0.01 vol%. Gradual temperature curing is then performed: after turning off vibration, cure at 80-90℃ for 2-3 hours, then increase the temperature to 120℃ at a rate of 1-2℃ / min and cure for 2-4 hours. After curing, annealing pretreatment is performed: treat at 150-250℃ for 30 minutes. Finally, cool to 60℃ at a cooling rate of 2-4℃ / min for demolding.
[0025] The beneficial effects of this invention are prominently reflected in: 1) Excellent high temperature resistance and acid corrosion resistance: It maintains high strength (≥ 40 MPa) under harsh conditions of 250 ℃ and can completely resist the corrosion of 50% sulfuric acid; 2) Ultra-low thermal deformation and dimensional stability: The deformation rate under heat transfer conditions is ≤ 0.03 mm / m; 3) Extreme densification: The innovative vibration venting process reduces the porosity of the material to an extremely low level (closed pore rate ≤ 0.05 vol%), which greatly improves mechanical properties and durability; 4) Optimized heat transfer interface: The surface roughness (Ra = 0.05 ~ 0.15 μm) is controlled by a specific annealing process, which significantly enhances the adhesion of the transfer layer (≥ 5.0 MPa) and the pattern fineness (≥ 400 dpi). Attached Figure Description
[0026] Figure 1 This is a scanning electron microscope (SEM) image of the interface of the anhydrous calcium sulfate whisker-reinforced high-temperature and acid-resistant artificial stone sample prepared in Example 1 of this invention, after being heat-treated at 250°C for 2 hours. As shown in the figure, the interface between the anhydrous calcium sulfate whiskers and the unsaturated resin matrix is intact, with no visible gaps or debonding. This indicates that even under high-temperature conditions, the whiskers and resin maintain a strong interfacial bond, which is direct evidence of the excellent high-temperature strength retention of the material of this invention.
[0027] Figure 2 The artificial stone sample prepared with traditional aluminum hydroxide filler in Comparative Example 4, in comparison with... Figure 1 Scanning electron microscope (SEM) images of the interface after the same heat treatment conditions. It is clearly visible that a distinct annular gap (i.e., interfacial debonding) has formed between the aluminum hydroxide filler and the resin matrix. This interfacial damage directly leads to stress transfer failure, causing a sharp decline in the material's mechanical properties at high temperatures.
[0028] Figure 3 The traditional quartz artificial stone sample prepared in Comparative Example 5, in comparison with... Figure 1 Scanning electron microscope (SEM) images of the interface after the same heat treatment conditions. As shown in the figure, obvious interfacial gaps also appeared between the quartz filler and the resin matrix. This proves that although the quartz filler itself is heat-resistant, its interface with the resin is also a thermodynamically weak link.
[0029] pass Figure 1 and Figure 2 , Figure 3 The comparison directly demonstrates that the anhydrous calcium sulfate whiskers used in this invention can significantly improve the high-temperature stability of the filler-resin interface, thereby solving the core technical problem of easy interface failure in traditional artificial stone at high temperatures. Specific Implementation
[0030] Example 1: Whisker reference set (70% content)
[0031] 1. Raw material ratio
[0032] Anhydrous calcium sulfate whiskers (calcined at 620 ℃, aspect ratio 15, 92% of crystals are 150 ~ 300 μm): 70%
[0033] Phthalate unsaturated resin (containing 12% MMA monomer): 28.5%; Methyl ethyl ketone peroxide curing agent: 0.6%
[0034] 2. Preparation process
[0035] Mixing: Under a vacuum of -0.06 MPa, mix at 25 rpm for 8 minutes, then increase the speed to 80 rpm and mix for 18 minutes.
[0036] Vibration exhaust:
[0037] Phase 1: Vibrate at 35 Hz and 0.3 mm amplitude for 12 minutes at 30 ℃;
[0038] Phase 2: Heat to 60 ℃, adjust to 15 Hz frequency and 0.1 mm amplitude vibration for 8 minutes (until the mirror reflection on the material surface disappears);
[0039] Curing: After turning off the vibration, keep at 85 ℃ for 2.5 hours, then increase the temperature to 120 ℃ at 1.5 ℃ / min and keep at that temperature for 3 hours;
[0040] Cooling and demolding: Cool down to 60°C at 3°C / min and remove the board.
[0041] 3. Performance Test Results
[0042] High temperature strength: flexural strength after 250 ℃ × 2 h is 42.1 MPa (initial value at room temperature is 43.3 MPa → retention rate is 97.2%).
[0043] Acid resistance: No corrosion spots were found on the surface after immersion in 50% sulfuric acid for 24 hours;
[0044] Heat transfer accuracy: substrate deformation rate at 230 ℃ is 0.021 mm / m, transfer layer adhesion is 5.6 MPa, and pattern resolution is 418 dpi;
[0045] Microstructure: Electron microscopy shows seamless bonding between whiskers and resin interface (see...) Figure 1 ).
[0046] Example 2: High whisker content (85%)
[0047] Preparation and testing:
[0048] Raw material ratio: whiskers 85%, resin 14.0%, curing agent 0.6%;
[0049] The process parameters are the same as in Example 1 (the vibration exhaust stage 2 is adjusted to 65 ℃ × 8 min).
[0050] result:
[0051] Strength at 250 ℃ × 2 h: 43.9 MPa (initial value at room temperature: 44.6 MPa → retention rate: 98.4%).
[0052] Acid resistance: No corrosion spots were found on the surface after immersion in 50% sulfuric acid for 24 hours;
[0053] Heat transfer accuracy: substrate deformation rate at 230 ℃ is 0.019 mm / m, transfer layer adhesion is 5.1 MPa, and pattern resolution is 415 dpi.
[0054] Example 3: Low whisker group (65% content)
[0055] Preparation and testing:
[0056] Raw material ratio: whiskers 65%, resin 33.8%, curing agent 0.6%;
[0057] The process parameters are the same as in Example 1;
[0058] result:
[0059] Strength at 250 ℃ × 2 h: 41.5 MPa (initial value at room temperature: 43.6 MPa → retention rate: 95.1%).
[0060] Acid resistance: No corrosion spots were found on the surface after immersion in 50% sulfuric acid for 24 hours;
[0061] Heat transfer accuracy: substrate deformation rate at 250 ℃ is 0.027 mm / m, transfer layer adhesion is 5.8 MPa, and pattern resolution is 425 dpi.
[0062] Comparative Example 1: Whiskers added at 50%
[0063] Preparation and testing:
[0064] Raw material ratio: whiskers 50%, resin 49.4%, curing agent 0.6%;
[0065] The process parameters are the same as in Example 1;
[0066] result:
[0067] Strength at 250 ℃ × 2 h: 32.6 MPa (initial value at room temperature: 38.4 MPa → retention rate: 84.9%).
[0068] Acid resistance: After immersion in 50% sulfuric acid for 24 hours, obvious corrosion spots were observed on the surface;
[0069] Heat transfer accuracy: substrate deformation rate at 250 ℃ is 0.054 mm / m, transfer layer adhesion is 4.4 MPa, and pattern resolution is 382 dpi.
[0070] Comparative Example 2: Whiskers added at 96%
[0071] Preparation and testing:
[0072] Raw material ratio: whiskers 96%, resin 3.4%, curing agent 0.6%;
[0073] The process parameters are the same as in Example 1;
[0074] result:
[0075] The amount of resin added was too small to achieve a bonding effect, and therefore it could not be used to make boards.
[0076] Comparative Example 3: Whisker aspect ratio 60, addition amount 70%
[0077] Preparation and testing:
[0078] Raw material ratio: whiskers 70%, resin 29.4%, curing agent 0.6%;
[0079] The process parameters are the same as in Example 1;
[0080] result:
[0081] Due to the increased aspect ratio of the whiskers, the mixing of whiskers and resin becomes more difficult, resulting in a decrease in the bending strength of the board. The strength at 250 ℃ for 2 h was 28.3 MPa (initial value at room temperature: 32.2 MPa → retention rate: 87.88%).
[0082] Comparative Example 4: Aluminum hydroxide as filler (70% filler)
[0083] Raw material ratio
[0084] Aluminum hydroxide (industrial grade, d50 = 10 μm): 70%; Phthalic unsaturated resin (containing 12% MMA monomer): 28.5%; Methyl ethyl ketone peroxide curing agent: 1.5%
[0085] Preparation process (same equipment and parameters as in Example 1)
[0086] Mixing: Vacuum degree -0.06 MPa, 25 rpm × 8 min → 80 rpm × 18 min;
[0087] Vibration exhaust:
[0088] Phase 1: 30 ℃ × 12 min (35 Hz, 0.3 mm amplitude)
[0089] Phase 2: 60 ℃ × 8 min (15 Hz, 0.1 mm amplitude) → Microbubble escape sound appears;
[0090] Curing: 85 ℃ × 2.5 h → increase temperature to 120 ℃ × 3 h at a rate of 1.5 ℃ / min;
[0091] Cooling and demolding: Cool to 60℃ at a rate of 3℃ / min. Demold.
[0092] Analysis results:
[0093] After 220 ℃ for 2 h, the strength plummeted to 14.3 MPa (only 50% of the initial value); electron microscopy revealed micropores and interfacial gaps. Figure 2 (The thermal transfer resolution is only 285 dpi).
[0094] Comparative Example 5: Quartz stone as filler (85% filler)
[0095] Raw material ratio
[0096] Quartz sand (200 mesh, SiO2 ≥ 99%): 85%; Phthalic unsaturated resin: 14.4%; Methyl ethyl ketone peroxide curing agent: 0.6%
[0097] Preparation process (same equipment and parameters as in Example 1)
[0098] Mixing: Vacuum degree -0.06 MPa, 25 rpm × 8 min → 80 rpm × 18 min;
[0099] Vibration exhaust:
[0100] Phase 1: 30 ℃ × 12 min (35 Hz, 0.3 mm amplitude)
[0101] Phase 2: 60 ℃ × 8 min (15 Hz, 0.1 mm amplitude) → Microbubble escape sound appears;
[0102] Curing: 85 ℃ × 2.5 h → increase temperature to 120 ℃ × 3 h at a rate of 1.5 ℃ / min;
[0103] Cooling and demolding: Cool to 60℃ at a rate of 3℃ / min. Demold.
[0104] Test results:
[0105] After 220 ℃ × 2 h, the strength plummeted to 14.3 MPa (only 50% of the initial value); the hot deformation rate at 250 ℃ was 0.13 mm / m (6 times that of this invention), and interfacial thermal stress cracks ( Figure 3 ).
Claims
1. A whisker-reinforced, high-temperature and acid-resistant artificial stone, characterized in that... Made from the following components: The amount of anhydrous calcium sulfate whiskers is 65% to 90%; the amount of unsaturated resin is 10% to 35%; the amount of curing agent is 0.2% to 1%; and the artificial stone simultaneously meets the following requirements: (a) after heating at 250 ℃ for 2 h, the flexural strength is ≥ 40 MPa and the strength retention rate is ≥ 95%; (b) after contact with 50% sulfuric acid for 24 h, there are no blemishes on the surface; (c) when the temperature is suitable for heat transfer process of 200 to 230 ℃, the substrate deformation rate is ≤ 0.03 mm / m.
2. The anhydrous calcium sulfate whisker-reinforced artificial stone as described in claim 1, characterized in that... The anhydrous calcium sulfate is calcined at 620-650 ℃, has an aspect ratio of 5-40, and a length of 150-300 μm accounts for ≥90%; the unsaturated resin component is an orthophthalic resin with added MMA monomer.
3. The application of the artificial stone as described in any one of claims 1-2 in heat transfer printing, characterized in that: At a transfer temperature of 190 ~ 230 ℃ and a pressure of 0.5 ~ 0.8 MPa, the adhesion of the transfer layer is ≥ 5.0 MPa and the pattern resolution is ≥ 400 dpi.
4. The method for preparing artificial stone according to any one of claims 1-2, comprising the following steps: (a) Mixing whiskers and resin in stages in a kneader (vacuum degree -0.01 ~ -0.09 MPa): First stage: Mix at 20-30 rpm for 5-10 minutes; Second stage: Mix at 70-90 rpm for 15-25 minutes; (b) Vacuum vibration exhaust: Stage 1: Vibrate continuously at 25 ~ 40 ℃ for 5 ~ 15 min, vibration frequency 30 ~ 50 Hz, amplitude 0.2 ~ 0.4 mm; Stage 2: Vibrate at 55 ~ 65 ℃, vibration frequency 10 ~ 20 Hz, amplitude 0.05 ~ 0.1 mm, then raise the temperature to 55 ~ 65 ℃ and vibrate for 5 ~ 10 min until the mirror reflection on the material surface disappears or there is no leveling in the needle scratch test; (c) Curing: Turn off the vibration, heat to 80~90 ℃ and cure for 2~3 h, then continue to increase the curing temperature to 120 ℃ and cure for 2~4 h; (d) Post-curing heat transfer pretreatment: Annealing at 150 ~ 250 ℃ for 30 min; (e) Demold after cooling to 60 °C.
5. The preparation method according to claim 4, characterized in that: After annealing, the surface roughness Ra of the substrate is 0.05 ~ 0.15 μm, and the bonding strength of the heat transfer is improved by 20% ~ 30%.
6. A specific method for applying vibration venting technology in the manufacture of artificial stone, characterized in that... Timing control includes: The vibration direction is perpendicular to the bottom surface of the mold. Exhaust stage 1: 25 ~ 40 ℃ × (5 ~ 20 min); Exhaust stage 2: 55 ~ 60 ℃ × (5 ~ 10 min). After vibration in the two stages, the closed-cell rate of the material is ≤ 0.05 vol%, and the open-cell rate is ≤ 0.01 vol.
7. As described in claim 3, after the second stage of vibration, the temperature rise and curing process control includes: Heat the mixture to 80-90℃ at a heating rate of 1-2℃ / min, hold for 2-4 hours, then heat to 110-120℃ at a heating rate of 1-2℃ / min, hold for 2-4 hours; cool to 60℃ at a cooling rate of 2-4℃ / min, and demold.
Citation Information
Patent Citations
High-impact-resistant artificial quartz stone plate and production process thereof
CN103204661A
Calcium sulfate-whisker compounded quartz stone board product and preparation method thereof
CN103408251A
A super-strong, wear-resistant artificial quartz stone slab and its preparation method
CN105948568B
Carbon fibre reinforced high thermal conductivity epoxy resin composite material for LED packaging and preparation method thereof
CN107474482A
High-performance artificial quartz plate
CN107805003A